Evaluation and Study of Pollution in The Elements in The Baiji Refinery After the Recent Terrorist Operations - Abdullah, Khairullah M (Journal for Research in Applied Sciences and Biotechnology, 2024)
The research is about the evaluation and study of heavy metal pollution in Baiji refinery after the recent terrorist operations. The samples were examined with an atomic absorption spectrometer (Atomic Absorption Spectrometer) model Shimadzu (AA6200) working with acetylene gas - in the laboratory of mechanical analysis - chemical engineering - Tikrit University, where the concentrations of heavy elements ranged (cadmium ≥ 4 mg/kg), nickel (16.8) - (4 mg/kg), copper (1.4-268.1) (mg/kg), zinc (21.6-554.8 mg/kg) and lead. (165.2 -2 mg/kg) (cobalt is less than (2 mg/kg), where the values ​​of the pollution coefficient showed the presence of a low pollution coefficient in most areas and most of the elements, while there was (a very high pollution coefficient of zinc in the area of ​​​​the loading arms, pumping and storage of fats Hydrogenation of fats, and less pollution of zinc (i.e., a significant pollution coefficient of zinc in the dewaxing division area), while the lead element was there (a very high pollution coefficient in the desalination of gases and northern refining), while for the copper element, there was significant pollution in the hydrogenation of fats. The results of laboratory tests have indicated that the values ​​of some of the heavy elements taken within this study were outside the permissible limits when compared with the approved determinants for zinc, copper, cobalt, and lead.